Bilateral Optic Neuritis in a Child with Acute Disseminated Encephalomyelitis: A Case Report - Wadhwani, Meenakshi; Kumar, Amit; Dhingra, Dhulika (Nepalese Journal of Ophthalmology, 2023)
Background: Acute disseminated encephalomyelitis is an inflammatory demyelinating disease of the central nervous system following a viral illness or vaccination, which occurs most often in children as a monophasic event. The neurological signs typically appear days to weeks after an initial febrile infection (usually of the upper respiratory tract) or vaccine immunisation. Case: An eight year old boy presented with painless progressive diminution of visual acuity for two days, On ophthalmic examination his visual acuity was hand movements at a close range in both the eyes. Posterior segment examination revealed bilateral optic disc swelling. Observations: Magnetic Resonance Imaging (MRI) brain revealed multiple discrete ovoid hyperintense lesions in bilateral cerebral white matter. His contrast enhanced MRI orbit study revealed bilateral oedematous optic nerve. Conclusion: Optic neuritis can present with different systemic conditions. Thorough ocular examinations (visual acuity, colour vision, contrast sensitivity, fundus examination) and neuroimaging should be done in all the cases. Early diagnosis and management is required for good visual prognosis.